Value of Forest Feed to Livestock in Lower Himalayas - Kumar, Vishwesh; Pandey, Rajiv (Indian Forester, 2009)
The result showed poor quality of life of the people of the Jaunsar region. The average size of livestock in terms of adult cattle units was 9.6 units. The estimated quantity of fodder was 35 kg per day per household with the average distance traveled was 1.54 km per day and spent time was 2.54 hours. The various parameters in particular family structure, assets, capital issues were correlated with willingness to pay for various categories of availability of fodder.